ERK1/2 and Akt phosphorylation were essential for MGF E peptide regulating cell morphology and mobility but not proangiogenic capacity of BMSCs under severe hypoxia. (13th February 2018) - Sha, Yongqiang; Yang, Li; Lv, Yonggang
Abstract : Severe hypoxia inhibits the adhesion and mobility of bone marrow‐derived mesenchymal stem cells (BMSCs) and limits their application in bone tissue engineering. In this study, CoCl2 was used to simulate severe hypoxia and the effects of mechano‐growth factor (MGF) E peptide on the morphology, adhesion, migration, and proangiogenic capacity of BMSCs under hypoxia were measured. It was demonstrated that severe hypoxia (500‐μM CoCl2 ) significantly caused cell contraction and reduced cell area, roundness, adhesion, and migration of BMSCs. RhoA and ROCK1 expression levels were upregulated by severe hypoxia, but p ‐RhoA and mobility‐relevant protein (integrin β1, p ‐FAK and fibronectin) expression levels in BMSCs were inhibited. Fortunately, MGF E peptide could restore all abovementioned indexes except RhoA expression. MEK‐ERK1/2 pathway was involved in MGF E peptide regulating cell morphological changes, mobility, and relevant proteins (except p ‐FAK). PI3K‐Akt pathway was involved in MGF E peptide regulating cell area, mobility, and relevant proteins. Besides, severe hypoxia upregulated vascular endothelial growth factor α expression but was harmful for proangiogenic capacity of BMSCs. Our study suggested that MGF E peptide might be helpful for the clinical application of tissue engineering strategy in bone defect repair. Significance of the study: Sever hypoxia impairs bone defect repair with bone marrow‐derived mesenchymal stem cells (BMSCs). This study proved that mechano‐growth factor E (MGF E) peptide could improve the severe hypoxia‐induced cell contraction and decline of cell adhesion and migration of BMSCs. Besides, MGF E peptide weakened the effects of severe hypoxia on the cytoskeleton arrangement‐ and mobility‐relevant protein expression levels in BMSCs. The underlying molecular mechanism was also verified. Finally, it was confirmed that MGF E peptide showed an adverse effect on the expression level of vascular endothelial growth factor α in BMSCs under severe hypoxia but could make up for this deficiency through accelerating cell proliferation.